Formulation of Pedagogical Strategy of Pai Teachers in Internalizing Empathy and Social Sensitivity of Students at Muhammadiyah 2 Junior High School Medan - Yusnifa Aini; Makmur Syukri (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze and formulate the pedagogical strategies of Islamic Religious Education (PAI) teachers in internalizing the values of empathy and social sensitivity among students at SMP Muhammadiyah 2 Medan. Amid the challenges of the digital era and the increasing individualistic behavior among adolescents, the role of PAI teachers becomes essential in shaping students' social character based on Islamic values. This study employed a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with PAI teachers, homeroom teachers, principals, and students, as well as documentation studies. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings revealed that the pedagogical strategies implemented by PAI teachers include: (1) habituation strategies through social and religious activities at school, (2) exemplary strategies (uswah hasanah) through teachers' daily behavior, and (3) dialogic-reflective strategies in the learning process by relating Islamic education materials to students' social realities. Supporting factors of these strategies include a school environment based on Al-Islam and Muhammadiyah values, while the inhibiting factors stem from the influence of social media and the low level of students' social interaction. The implications of this study indicate that consistently implemented pedagogical strategies are capable of enhancing students' empathy and social sensitivity within the school environment.